Multicenter Study of Resistant Arterial Hypertension Course After Classic and Eversion Carotid Endarterectomy - A. N. Kazantsev; R. A. Vinogradov; M. A. Chernyavsky; V. N. Kravchuk; D. V. Shmatov; A. A. Sorokin; A. A. Erofeyev; V. A. Lutsenko; R. V. Sultanov; A. R. Shabayev; I. M. Radjabov; G. Sh. Bagdavadze; et al. (Неотложная медицинская помощь)
Aim of study. Analysis of the dynamics of resistant arterial hypertension (RAH) and the spectrum of adverse cardiovascular events in patients after classical carotid endarterectomy (CEE) with preservation of carotid body (CB) and eversion CEE with CB transection.Material and methods. This cohort, comparative, retrospective, open-label study from January 2014 to December 2020 included 761 patients with hemodynamically significant stenosis of the internal carotid arteries (ICA) and RH lasting more than 3 years. Depending on the implemented revascularization strategy, 2 groups were formed: Group 1: 38.0% (n=289) — classical CEE with plasty of the reconstruction zone with a patch (made of diepoxy-treated xenopericardium or synthetic); Group 2: 62% (n=472) — eversion CEE with CB transection. To study the dynamics of systolic blood pressure (SBP) in the preoperative period for 4 days, and in the postoperative period, blood pressure was measured for 10 days (during the period when the patient was in intensive care - according to daily monitoring of blood pressure; in the department - 10 times per day, daily). The average SBP figures for all patients were taken into account when constructing a graph of BP fluctuations.Results. In the postoperative period, the groups were comparable in the frequency of the following events: death (group 1: 0.34% (n=1), group 2: 0.63% (n=3); p=0.98; OR 0.54; 95% CI 0.05–5.21), myocardial infarction (group 1: 0.34% (n=1), group 2: 0.84% (n=4); p=0.71; OR 0, 40; 95% CI 0.04–3.65), ischemic stroke (group 1: 0.34% (n=1), group 2: 1.27% (n=6); p=0.36; OR 0.26; 95% CI 0.03–2.25), hemorrhagic transformation (group 1: 0%, group 2: 0.84% (n=4); p=0.29; OR 0.17; 95% CI 0.009–3.35). However, in terms of the number of all complications (death + myocardial infarction + ischemic stroke + hemorrhagic transformation) presented as a combined endpoint, patients after eversion CEE with CB transection were three times superior to classical surgery (group 1: 1.03% (n=3 ), group 2: 3.60% (n=17); p=0.05; OR 0.28; 95% CI 0.08–0.9).Conclusion. The choice of a revascularization strategy in patients with hemodynamically significant ICA stenosis should be personalized and based on the conclusion of a multidisciplinary consultation, and not only on the preferences of the operating surgeon. In patients with RH, it is more expedient to use classical CEE with plasty of the reconstruction zone with a patch in view of the preservation of the CB during this operation. The intersection of the latter with eversion CEE provokes labile hypertension, progression of RAH and a statistically significant increase in the number of all unfavorable cardiovascular events. Thus, the use of carotid body preserving CEE in patients with RAH confirms the therapeutic mechanism of this manipulation in achieving the target SBP level.